2018
DOI: 10.1177/1055665618776074
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Obstructive Sleep Apnea, Nasal Obstruction, and Enuresis in Children With Nonsyndromic Cleft Lip and Palate: A Prevalence Study

Abstract: Children with nonsyndromic cleft lip and palate have high prevalence of nasal obstruction and enuresis and are at risk of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 62 publications
1
27
2
Order By: Relevance
“…Nasal congestion is considered to be a major factor interfering with sleep quality and inducing daytime somnolence. Previous studies suggest that nasal obstruction contributes to higher risks of OSA [48][49][50] and SDB [51,52]. The role of nasal congestion as a risk factor for snoring has also been confirmed by a population-based cohort study [53].…”
Section: Assessment Of Cumulative Evidencementioning
confidence: 70%
“…Nasal congestion is considered to be a major factor interfering with sleep quality and inducing daytime somnolence. Previous studies suggest that nasal obstruction contributes to higher risks of OSA [48][49][50] and SDB [51,52]. The role of nasal congestion as a risk factor for snoring has also been confirmed by a population-based cohort study [53].…”
Section: Assessment Of Cumulative Evidencementioning
confidence: 70%
“…According to the American Academy of Otolaryngology–Head and Neck Surgery (AAO–HNS), polysomnography is the gold standard for diagnosing sleep‐disordered breathing in children, including OSA. 23 Polysomnography is recommended before tonsillectomy in children with SDB who have conditions that increase their risk for complications of surgery, such as obesity, Down syndrome, 23 , 24 craniofacial abnormalities (eg, Pierre‐Robin sequence and cleft palate), 23 , 25 , 26 neuromuscular disorders (eg, muscular dystrophy), sickle cell disease (SCD), or mucopolysaccharidoses. 23 Children with Down syndrome have adenotonsillar hypertrophy, midface and mandibular hypoplasia, relative macroglossia, glossoptosis, generalized muscular hypotonia, and obesity, increasing their risk for airway obstruction.…”
Section: Diagnostic Evaluation Of Sdb and Osa Syndromementioning
confidence: 99%
“…Several studies have indicated an association between nasal obstruction and increased risk of RSD, with a prevalence of this symptom being observed in up to 50% of non-syndromic patients diagnosed with OSA. 9 , 10 , 11 , 12 It is speculated that the airflow decreases during sleep, due to nasal pathologies, generates progressive negative pressures in the upper airways (UA), facilitating pharyngeal collapse, and, consequently, snoring, obstructive apnea, sleep fragmentation and excessive daytime sleepiness. 10 The relationship between the nasal obstruction intensity and greater severity and occurrence of OSA, however, remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, patients with PRS show morphological alterations that increase the risk of OSA at different stages of life. 11 , 15 Moreover, it should be noted that the primary corrective surgery of the palate may further compromise the nasal and pharyngeal dimensions, generating a higher risk for RSD in this population. 6 , 11 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation